2014
DOI: 10.1007/s00217-014-2256-2
|View full text |Cite
|
Sign up to set email alerts
|

1-Methylcyclopropene postharvest treatment and their effect on apple quality during long-term storage time

Abstract: instrumental measurements. The results of presented study demonstrate that apples after storage, especially 'Shampion' cv., can be a valuable sensory attributes for food product and consumption. This study indicates that the use of 1-MCP treatment in long-term storage of apples is promising for maintaining the eating quality of fruits, however, in some extent may affect their antioxidant compounds content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
(35 reference statements)
4
27
0
Order By: Relevance
“…Assessment of the dry-matter content of the chokeberry fruit was performed by means of a gravimetric method [16]. The fresh chokeberry samples were precisely weighed (1.5 g) and dried at a temperature of 70 • C under 3 kPa vacuum pressure until a constant weight was obtained.…”
Section: Dry-matter and Ash Content And Water Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the dry-matter content of the chokeberry fruit was performed by means of a gravimetric method [16]. The fresh chokeberry samples were precisely weighed (1.5 g) and dried at a temperature of 70 • C under 3 kPa vacuum pressure until a constant weight was obtained.…”
Section: Dry-matter and Ash Content And Water Activitymentioning
confidence: 99%
“…Flavan-3-ols include monomeric (catechins) and polymeric (procyanidins) forms mainly constituted by (-)-epicatechin units. Among the hydroxycinnamic acids, 5-caffeoylquinic acid and 4-p-coumaroylquinic acid are present in the highest concentrations [16]. Apple juice is an important component of fruit intake in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the quality of produced 'Szampion' cultivar apples, various actions are taken, including spraying trees [2], modified atmosphere storage [3], and edible coatings [4], but also postharvest treatment by 1-methylcyclopropene (1-MCP) [5]. 1-MCP is commonly used in postharvest treatment also for other cultivars, such as 'Aroma', 'Red Gravenstein', 'Summered Norvegian' [6], 'Idared' [5], 'Granny Smith' [7], 'Red Delicious' [8], 'Cripps Pink' [9], and 'Jonah King' cultivars [10]. It inhibits ripening of climacteric fruit by blocking ethylene receptors, preventing ethylene from binding and eliciting its action [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many countries in the world have been using 1‐MCP in the postharvest preservation of fruits, vegetables, and flowers, e.g., apple (Kolniak‐Ostek et al . ), banana (Pathak et al . ), tomato (Paul and Pander ), strawberry (Tian et al .…”
Section: Introductionmentioning
confidence: 99%
“…1-Methylcyclopropene (1-MCP) is a new ethylene inhibitor (Sisler et al 1996), which has been found to be able to effectively regulate fruit maturation and prolong fruit shelf-life. Many countries in the world have been using 1-MCP in the postharvest preservation of fruits, vegetables, and flowers, e.g., apple (Kolniak-Ostek et al 2014), banana (Pathak et al 2003), tomato (Paul and Pander 2013), strawberry (Tian et al 2014), and fresh flowers (Seglie 2011). ClO 2 is a strong oxidant with extremely high germicidal activity, and it leaves no harmful substances or odor residuals after treating fruits and vegetables; thus, the fruits and vegetables retain their own flavors and external qualities.…”
Section: Introductionmentioning
confidence: 99%